2014
DOI: 10.4103/0972-5229.126077
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in critically ill patients

Abstract: Context:Hyponatremia is a common electrolyte disturbance in critically ill hence understanding its implications is important.Aims:This study was carried out to ascertain frequency, predisposing conditions and outcome in critically ill patients with hyponatremia on intensive care unit (ICU) admission.Settings and Design:This was an observational, prospective study of a series of ICU patients during a 12-month period.Materials and Methods:The patients were divided into two groups: Hyponatremic (serum sodium < 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 16 publications
2
49
0
Order By: Relevance
“…This observation is similar to study done by Padhi R et al in which septicemia was the leading cause of hyponatremia in this study; no significant difference was noted in study groups regarding serum sodium levels. 4 Already admitted subjects showed significantly higher duration of illness (23.7±59.3 days) compared to newly admitted subjects (9.4±19.8 days) (p <0.01). Frequency of subjects with different systems involved was noted in both study groups.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This observation is similar to study done by Padhi R et al in which septicemia was the leading cause of hyponatremia in this study; no significant difference was noted in study groups regarding serum sodium levels. 4 Already admitted subjects showed significantly higher duration of illness (23.7±59.3 days) compared to newly admitted subjects (9.4±19.8 days) (p <0.01). Frequency of subjects with different systems involved was noted in both study groups.…”
Section: Discussionmentioning
confidence: 86%
“…Padhi R et al conducted a prospective study of series of ICU patient for 12 month period in total 730 patients and found the frequency of hyponatremia on ICU admission was 34.3%. 4 Alicia K. Au et al performed a retrospective analysis of postoperative admission to pediatric intensive care unit in total 145 children (116 received hypotonic and 29 received normotonic fluid) 11% were hyponatremic. 8 A study by Fenk et al involving 151486 adult patients from 77 ICU's over 10 years noted that severity of hyponatremis in ICU is associated with poor outcome in graded fashion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Prevalence of hyponatraemic patients is 3.5%-40.0%. [2][3][4] The commonest cause of euvolemic hyponatremia is SIADH, other causes being diuretics, CCF and liver disorder, etc. [5][6] Hyponatremia is classified as hypovolemic, euvolemic and hypervolemic.…”
Section: Introductionmentioning
confidence: 99%